Behind the scenes Contemporary bollywood directors and their cinema - Viswamohan, Aysha Iqbal; Viswamohan, Aysha Iqbal (New Delhi SAGE Publications, 2017)
Cinema of glamour and celebration : The post-liberalization bollywood auteur